Conservative concept of the national state H. Ortega y Gаsset - Oleh Turenko (Cхід)
The nature and factors of the existence of the nation-state in the doctrine of H. Ortega y Gasset are revealed. Ortehovoyi in interpreting the nation-state is a metaphysical strength and unity of past and future, tradition (lifestyle) and consolidating new purpose-idea alloy democratic institutions and subconscious zovu blood, land, language, mature nation. As an instrument of the nation, the nation state is a political entity that legitimizes the idea of social order and public self is an initiative of the people and personality. The democratic nature of the nation-state is its indispensable advantage - it gives real grounds separate individual and values harmonious collective resist oppression.